A management-oriented water quality model for data scarce catchments. (November 2017) - Slaughter, A.R.; Hughes, D.A.; Retief, D.C.H.; Mantel, S.K.
Abstract: Due to the degeneration of water quality globally, water quality models could increasingly be utilised within water resource management. However, a lack of observed data as well as financial resources often constrain the number of potential water quality models that could practically be utilised. This study presents the Water Quality Systems Assessment Model (WQSAM). WQSAM directly utilises flow data generated by systems models to drive water quality simulations. The model subscribes to requisite simplicity by constraining the number of variables simulated as well as the processes represented to only those most important to water quality management, in this case, nutrients and salinity. The model application to the upper Olifants River catchment in South Africa is described. WQSAM was able to use the limited observed data to simulate representative frequency distributions of water quality, and the approach used within WQSAM was shown to be suitable for application to data scarce catchments. Highlights: A water quality model (WQSAM) based on requisite simplicity is described. The model was applied to a data scarce catchment in South Africa. The water quality simulations obtained were mostly representative of observed data. Usefulness, uncertainties and potential extensions of the model are described.